PENGARUH RISIKO KREDIT, TINGKAT SUKU BUNGA DAN TINGKAT KECUKUPAN MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015 - Wahyu Arianti; Budi Wahono; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe research has a purpose to determine the effect of simultaneous andpartial credit risk, interest rate and capital adequacy rate on profitability atcompanies listed on the Indonesia Stocks ExchangeTe technique used is purposesampling with the criteria of banking companies listed on the Indonesia StocksExchange in the period 2013-2015. Obtained a number of samples of 21 bankingcompanies.The method used in this research is deskriptif statistical test, normalitytest, multiple linear regression test, clasiccal assumption test that includesmultikolonierity test, autocorrelation test and heterokedastisity test andhypothesis test that includes partial and simultaneous test.The result of this study indicate that 1) credit risk has a significantnegative effect on profitability in banking companies listed on the IndonesiaStocks Exchange in 2013-2015, 2) interest rates have an insignificant negativeeffect on profitability on banking companies listed on the Indonesia StocksExchange in 2013-2015, 3) the level of capital adequacy has a significant positiveeffect on profitability in banking companies listed on the Indonesia StocksExchange in 2013-2015.Keyword : Credit Risk, Interest Rates, Capital Adequacy and Profitability.